2013
DOI: 10.1080/19443994.2013.846234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of operating parameters and additives on degradation of phenol in water by the combination of H2O2and hydrodynamic cavitation

Abstract: A B S T R A C TThe combination of H 2 O 2 and hydrodynamic cavitation has been used to degrade phenol in water. The effects of parameters including inlet pressure (P1), orifice geometries of hydrodynamic reactor, initial concentration of H 2 O 2 , the presence of dissolved gases and catalysts (CuO, Fe, and TiO 2 ) have been discussed. It revealed that increased P1, more number of holes on plates, optimum initial H 2 O 2 concentration, the higher flow rate of oxygen, and the presence of Fe or CuO are more favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…The microbubbles can grow continuously until they reach a critical size, which can cause a violent implosive collapse. The rapid implosion of cavitation bubbles is followed by a localized extremely high temperature and high pressure of about 5000 °C and 500 atm, respectively [135][136][137]. Under this kind of extreme conditions water can be transformed into different oxidizing species via pyrolysis, such as H•, HO•, HO2 -•, and H2O2 [44,138].…”
Section: Cavitation-fenton-like Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbubbles can grow continuously until they reach a critical size, which can cause a violent implosive collapse. The rapid implosion of cavitation bubbles is followed by a localized extremely high temperature and high pressure of about 5000 °C and 500 atm, respectively [135][136][137]. Under this kind of extreme conditions water can be transformed into different oxidizing species via pyrolysis, such as H•, HO•, HO2 -•, and H2O2 [44,138].…”
Section: Cavitation-fenton-like Processesmentioning
confidence: 99%
“…A typical scheme for acoustic cavitation and an ultrasonic-Fenton/Fenton-like system are shown in Figure 7 and Figure 8, respectively. The hydrodynamic cavitation can be generated by the orifice plate and/or slit venturi at the laboratory scale [133,134,137]. In the liquid-solid system, however, the mechanism of enhancing Fenton-like processes by the cavitation bubbles is different from that in the homogeneous system mentioned above.…”
Section: Cavitation-fenton-like Processesmentioning
confidence: 99%
“…In a study of phenol degradation, Wu et al . [41] varied the gas atmosphere with nitrogen and oxygen, and compared it with their baseline conditions. Of the five datasets presented, the sparging of nitrogen (0.05 L/min N 2 , in 70 L) was the only one which seemed to alter the degradation of phenol, lowering it from 22.5 to 15 % in 90 min.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, when compared to the cavity bubble-induced oxidation reactor, HC provides slightly higher degradation. Wu et al (2015) reported 27.2% degradation of phenol using a combination of HC (multiple orifice plates) and TiO 2 (anatase to rutile, 3:1). The results of the cavity bubble-induced oxidation reactor are also consistent with Taylor et al (2015).…”
Section: Effect Of Optimal Loading Of Tiomentioning
confidence: 99%